A Case of Apparent Upper-Body Freezing in Parkinsonism while Using a Wheelchair - Nemanich, Samuel T.; McNeely, Marie E.; Earhart, Gammon M.; Norris, Scott A.; Black, Kevin J. (Frontiers in Neurology, 2017)
Freezing of gait (FOG) is a common, disabling gait disturbance in Parkinson disease (PD) and other Parkinsonian syndromes. Freezing also occurs during non-gait movements involving the upper limbs. The mechanisms underlying freezing are complex, likely involving motor, cognitive, and sensory systems that contribute to the episodes. Here we report a 60 year old female with a 24-year history of parkinsonism who experienced significant FOG when ambulatory. Disease progression resulted in her permanent use of a powered wheelchair. While using the power chair, the patient experiences apparent paroxysmal freezing in the hand and arm used to steer and propel the chair. These episodes, some lasting up to several minutes, occur only in circumstances (e.g. entering and leaving an elevator) that are similar to environments known to elicit and exacerbate FOG. Episodes are transient and can be volitionally interrupted by the patient but sometimes require external assistance. Therapeutic intervention for this type of potential freezing has yet to be determined. This case may provide insight into the complex nature of freezing behavior and suggests a need for new approaches to treating non-traditional freezing behavior.